Rapid Method in Identification of Clostridium perfringens in Foods by Reverse CAMP Test - Siriporn Stonsaovapak; Supannee Chitpinityol; Wannee Somporn (Agriculture and Natural Resources, 1993)
Ninety-seven percent of Clostridium perfringens isolated from various kinds of food were reverse CAMP test positive. C. perfringens was detected by inoculation at right angles to within 1 to 2 mm. of a β-hemolytic group B Streptococcus agalactiae on sheep blood agar. A positive test was indicated by the formation of an arrowhead-shaped hemolytic pattern at the junction of the two cultures. The reverse CAMP test significantly reduces the time and cost for identifying C. perfringens frequently isolated from food.